Early-Onset Network Hyperexcitability in Presymptomatic Alzheimer’s Disease Transgenic Mice Is Suppressed by Passive Immunization with Anti-Human APP/Aβ Antibody and by mGluR5 Blockade - Kazim, Syed F.; Chuang, Shih-Chieh; Zhao, Wangfa; Wong, Robert K. S.; Bianchi, Riccardo; Iqbal, Khalid (Frontiers in Aging Neuroscience, 2017)
Cortical and hippocampal network hyperexcitability appears to be an early event in Alzheimer’s disease (AD) pathogenesis, and may contribute to memory impairment. It remains unclear if network hyperexcitability precedes memory impairment in mouse models of AD and what are the underlying cellular mechanisms. We thus evaluated seizure susceptibility and hippocampal network hyperexcitability at ~ 3 weeks of age [prior to amyloid β (Aβ) plaque deposition, neurofibrillary pathology, and cognitive impairment] in a triple transgenic mouse model of familial AD (3xTg-AD mouse) that harbors mutated human amyloid β precursor protein (APP), tau, and presenilin 1 (PS1) genes. Audiogenic seizures were elicited in a higher proportion of 3xTg-AD mice compared with wild type (WT) controls. Seizure susceptibility in 3xTg-AD mice was attenuated either by passive immunization with anti-human APP/Aβ antibody (6E10) or by blockade of metabotropic glutamate receptor 5 (mGluR5) with the selective antagonist, 2-methyl-6-(phenylethynyl)pyridine hydrochloride, MPEP. In in vitro hippocampal slices, suppression of synaptic inhibition with the GABAA receptor antagonist, bicuculline, induced prolonged epileptiform (>1.5 s in duration) ictal-like discharges in the CA3 neuronal network in the majority of the slices from 3xTg-AD mice. In contrast, only short epileptiform (<1.5 s in duration) interictal-like discharges were observed following bicuculline application in the CA3 region of WT slices. The ictal-like activity in CA3 region of the hippocampus was significantly reduced in the 6E10-immunized compared to the saline-treated 3xTg-AD mice. MPEP acutely suppressed the ictal-like discharges in 3xTg-AD slices. Remarkably, epileptiform discharge duration positively correlated with intraneuronal human (transgenic) APP/Aβ expression in the CA3 region of the hippocampus. Our data suggest that in a mouse model of familial AD, hypersynchronous network activity underlying seizure susceptibility precedes Aβ plaque pathology and memory impairment. This early-onset network hyperexcitability can be suppressed by passive immunization with an anti-human APP/Aβ antibody and by mGluR5 blockade in 3xTg-AD mice.